Financial Reporting Quality of Chinese Reverse Merger Firms: The Reverse Merger Effect or the Weak Country Effect? - Chen, Kun-Chih; Cheng, Qiang; Lin, Ying Chou; Lin, Yu-Chen; Xiao, Xing (The Accounting Review, 2016)
ABSTRACT In this paper, we examine why Chinese reverse merger (RM) firms have lower financial reporting quality than U.S. IPO firms. We find that the financial reporting quality of U.S. RM firms is similar to that of matched U.S. IPO firms, but Chinese RM firms exhibit lower financial reporting quality than Chinese ADR firms. We also find that Chinese RM firms exhibit lower financial reporting quality than U.S. RM firms. These results indicate that the use of the RM process is associated with poor financial reporting quality only in firms from China, where legal enforcement and investor protection are weak. In addition, we find that compared with Chinese ADR firms, Chinese RM firms have weaker bonding incentives (as measured by CEO turnover-performance sensitivity) and poorer corporate governance. These factors, in turn, contribute to the lower financial reporting quality of Chinese RM firms. Overall, our results suggest that the less scrutinized RM process allows the Chinese firms with weak bonding incentives and poor governance to gain access to U.S. capital markets, resulting in poor financial reporting quality. JEL Classifications: G15; G24; G34; G38.